The Idea of Pasundan Province 1926: Between Colonial Decentralization and the Politics of Identity - Mumuh Muhsin Zakaria; Abdul Rasyad (Universitas Hamzanwadi, 2026)
The idea of establishing the Pasundan Province in 1926 marked a crucial moment in the history of the colonial administration of the Dutch East Indies, bringing together the policy of decentralization (bestuurshervorming) with the dynamics of local identity politics. This article analyzes the complexities behind the formation of the Pasundan Province as a response to the colonial elite's fear of the political dominance of a specific ethnic group, as well as a manifestation of the sociopolitical aspirations of the Sundanese people. Utilizing critical historical methods—including heuristics, source criticism, interpretation, and historiography—this study explores colonial archives, periodical publications (de Locomotief, Bataviaasch Nieuwsblad), and contemporary local documents. Theoretically, this article applies Furnivall's concept of colonial decentralization alongside modern political sociology theories of identity politics. The novelty of this article lies in its deconstruction of the singular narrative of decentralization; rather than viewing it merely as a matter of bureaucratic efficiency, this study demonstrates that the 1926 Pasundan Province was designed as an instrument of geopolitical engineering to curb nationalist radicalism while mapping ethno-regional boundaries. The findings indicate that the fear of identity politics dominance—both from the colonial government's perspective regarding Pan-Islamism and communism, and the Sundanese elite's anxiety over Javanese cultural dominance—served as the primary catalyst accelerating the realization of this province.